Species Abundance and Food Preferences of Butterflies Imago (Lepidoptera: Nymphalidae) at Utilization Block, Kerandangan Nature Tourism Park - Seftira, Lora Agista; Syaputra, Maiser; Indriyatno, Indriyatno (Jurnal Biologi Tropis, 2025)
This research was conducted in the Utilization Block of the Kerandangan Nature Tourism Park, West Lombok, to analyze the abundance and feeding preferences of butterflies of the family Nymphalidae. The background of the study is based on the important role of butterflies as pollinators as well as bioindicators of ecosystem health, and the limited recent data regarding their diversity in this area. The methods used include species identification using the time search technique and vegetation analysis using double-square plots to determine the types of host plants. The data were analyzed descriptively and quantitatively through diversity, evenness, species richness, similarity, dominance indices, as well as feeding preferences and importance value indices. The study recorded 112 individuals from 28 butterfly species. The habitat with the highest abundance was Open Spaces (35 individuals, 17 species), while the lowest was in Secondary Forest (12 individuals, 8 species). The highest Shannon-Wiener diversity index was recorded in Open Areas (H’=2.73; moderate category). Butterfly feeding preferences were dominated by flowers from the families Asteraceae, Acanthaceae, Fabaceae, Moraceae, and Apocynaceae, with Ageratum conyzoides being the most preferred nectar source. Around 90% of butterflies used flowers as an energy source, while 10% consumed decaying fruit. In conclusion, the Kerandangan Nature Reserve has a fairly high diversity of Nymphalidae butterflies, with the availability of flowering vegetation being a key factor in species abundance and distribution.